PEMETAAN DIGITAL POTENSI WISATA ALAM DAN BUDAYA DENGAN GIS UNTUK MENDUKUNG PENGELOLAAN DESA WISATA NEGERI SULI - Merlin Renny Sitanala; Willem Anthon Siahaya; Ronny Loppies (MARSEGU : Jurnal Sains dan Teknologi, 2025)
Negeri Suli Maluku Province, has various natural and cultural tourism potentials that can be developed into leading tourist destinations. This study aims to identify the natural and cultural tourism potential in Negeri Suli and map the existing tourist attractions using Geographic Information System (GIS). The data used in this research consists of primary data, obtained through direct observation and interviews with local communities, and secondary data from relevant institutions. The analysis used a qualitative descriptive approach, with mapping performed using ArcGIS 10.6 software. The results of the study show that Negeri Suli has a variety of tourist attractions, including beach tourism, land-based natural tourism, and cultural tourism. The use of GIS in mapping tourism objects provides spatial visualization that can be used as a basis for developing a tourist village. This study recommends improving tourism infrastructure and digital-based promotional strategies to attract more tourists.